2019
DOI: 10.1055/s-0039-1683869
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of Severe Anaphylaxis in Paediatric Patients in Atlantic Canada

Abstract: Little is known about severe anaphylaxis in the pediatric population. In this retrospective cohort study, we aimed to describe the characteristics of children who required admission from an outpatient setting to one of two Pediatric Intensive Care Units in Atlantic Canada with a primary diagnosis of anaphylaxis. During the 10-year study period, there were 12 admissions (58% females) for a population incidence of 2.4 per 100,000 children. Both patients who died were adolescents with a witnessed anaphylaxis even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Severe anaphylaxis requiring ICU admission is a rare event and difficult to study since the number of affected patients is usually small [32]. We identified that 10.57% of children with anaphylaxis required admission to the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Severe anaphylaxis requiring ICU admission is a rare event and difficult to study since the number of affected patients is usually small [32]. We identified that 10.57% of children with anaphylaxis required admission to the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…The timely administration of epinephrine is important in pediatric anaphylaxis since it can prevent hospitalization and fatalities [ 12 , 28 ]. However, the lack of a standardized protocol, low awareness of guidelines, and concern about side effects can all cause delays in epinephrine administration [ 19 ].…”
Section: Discussionmentioning
confidence: 99%